내측 개방형 근위경골절골술에서 교정 정확성을 높이기 위한 단계적 방법 - 조준희(Joon Hee Cho); 나경욱(Kyung Wook Nha); 이용석(Yong Seuk Lee) (The journal of the Korean Orthopaedic Association, 2023)
내측 개방형 근위경골절골술은 슬관절의 내반 변형을 동반한 내측 구획의 관절염을 치료하는 데 선호되는 수술방법이다. 이는 하지 정렬의 역학적 축을 변경하여 슬관절 내측 구획의 부하를 줄여줌으로써 환자의 통증을 경감시키고, 기능을 회복시키는 데 목적이 있다. 절골술 시행 시 주로 골 변형에 초점을 맞추어 수술의 교정 목표 계획이 수립되는데 관절 연골 상태와 연부조직에 대한고려가 충분히 이루어지지 않는다면 부정확한 교정 결과가 발생할 수 있다. 이 외에도 부정확한 교정의 원인으로는 잘못된 수술전 계획, 부정확한 절골 술기 및 부적절한 연부조직의 조치 등이 있다. 본 종설에서는 내측 개방형 근위경골절골술 시행 시 변형의평가, 교정 목표의 결정, 수술 전 계획, 수술 중 조정의 단계로 나누어 교정의 정확성을 향상시키기 위한 단계별 방법에 대해 다루고자 한다. Medial opening wedge high tibial osteotomy is the preferred surgical procedure for the treatment of medial compartmental osteoarthritis with a varus deformity. The purpose of this treatment is to reduce the load on the medial compartment by changing the alignment, thereby relieving the pain, and restoring function. However, deformity correction is mainly based on the bony deformity and this strategy can induce an inaccurate correction. The main cause of this inaccurate correction may be ignorance of the status of the soft tissue and the cartilage. In addition, inaccurate correction can be caused by improper planning, inappropriate osteotomy, and inadequate soft tissue management. In this review, we describe a step-by-step method to achieve optimal accuracy by dividing the process into deformity evaluation, determination of correction goals, preoperative planning, and intraoperative adjustment. KCI Citation Count: 0